Blue or far-red light supplementation induced pre-hardening in the leaves of the Rht12 wheat dwarfing line: hormonal changes and freezing tolerance - Gulyás, Zsolt; Ahres, Mohamed; Pálmai, Tamás; Kulman, Kitti; Tahmasebi, Zahra; Singh, Kalpita; Jobbágy, Kristóf; Tarkowská, Danuše; Dobrev, Petre; Vanková, Radomíra; Borbély, Péter; Börner, Andreas; et al. (Physiologia plantarum, 2025)
Reduced height (Rht) genes have revolutionised wheat cultivation, but they can compromise freezing tolerance, and only a few alleles are in use. Thus, evaluating the role of other Rht alleles in stress responses is crucial. Far-red supplementation of white light (W+FR) can induce pre-hardening in cereals at 15°C. However, the relevant effect of blue light enrichment (W+B) is poorly described. This study investigates the influence of W+FR or W+B exposure in young winter wheat leaves of a tall (wild-type, rht12) and a dwarf, gibberellin-deficient (near-isogenic line, Rht12) genotype in cv. Maris Huntsman background over 10 days at 15°C. The main objectives were to investigate the relationship between light quality, gibberellin homeostasis, and freezing tolerance. Key parameters such as frost injury, hormonal pools and the expression of relevant genes were examined. Results provided evidence about the involvement of Rht alleles in the basal freezing tolerance of wheat leaves from the side of gibberellin availability. It was revealed that W+FR and W+B treatments partially rescued the freezing-sensitive phenotype of Rht12 leaves, suggesting a potential compensatory mechanism. Analysis of gibberellic acid (GA) metabolism indicated differential responses to light treatments between the Rht12 and wild-type leaves, with implications for freezing tolerance. Moreover, alterations in hormone levels, including jasmonic acid (JA) and salicylic acid (SA), were observed, highlighting the complex interplay between light signalling and hormonal regulation in wheat. Overall, these findings suggest that manipulating light responses may offer a strategy to enhance freezing tolerance in gibberellin-deficient dwarf wheat genotypes.
Keywords: oxylipiny; Gene Expression Regulation, Plant; genotyp; Freezing; Light; Genotype; Oxylipins; červené světlo; Plant Leaves; světlo; regulátory růstu rostlin; Gibberellins; pšenice; Cyclopentanes; Red Light; gibereliny; regulace genové exprese u rostlin; zmrazování; Triticum; Plant Growth Regulators; cyklopentany; listy rostlin